Cancer‐related follow‐up care among Hispanic and non‐Hispanic childhood cancer survivors: The Project Forward study. Issue 4 (23rd October 2014) - Milam, Joel E.; Meeske, Kathleen; Slaughter, Rhona I.; Sherman‐Bien, Sandra; Ritt‐Olson, Anamara; Kuperberg, Aura; Freyer, David R.; Hamilton, Ann S.
Abstract : BACKGROUND: Follow‐up care is critical for childhood cancer survivors (CCS), who are at high risk for comorbidities and late effects of cancer treatments. Understanding the factors associated with maintaining follow‐up care is needed, especially for Hispanic CCS, who have been under‐represented in previous studies. METHODS: Risk factors and protective factors for receiving cancer‐related follow‐up care were examined among 193 Los Angeles County CCS diagnosed between 2000 and 2007 (54% Hispanic; mean ± standard deviation age, 19.9 ± 2.8 years; age at diagnosis, 12.1 ± 3.0 years; time since diagnosis, 7.8 ± 2.0 years). Self‐report surveys were used to assess follow‐up care, insurance status, demographics, clinical factors, and psychosocial risk (eg, depression) and protective (eg, self‐efficacy [SE]) factors. Multivariable logistic regression was used to identify factors associated with the previous receipt of cancer‐related follow‐up care (in prior 2 years) and the intent to seek future cancer‐related follow‐up care. RESULTS: Seventy‐three percent of CCS reported a cancer follow‐up visit in the previous 2 years, which was positively associated ( P  < .05) with having health insurance, white ethnicity (vs Hispanic), younger age, and greater treatment intensity. Sixty‐nine percent reported an intent to receive follow‐up care in the next 2 years, which was positively associated ( P  < .05) with having health insurance and greater SE. CONCLUSIONS: Hispanics and older CCS were more likely to lack previous follow‐up care. Because health insurance was strongly associated with both previous follow‐up care and the intent to seek care, the current results indicate that recent changes in health coverage may improve follow‐up among CCS. Interventions targeting improved SE may help increase intent to receive follow‐up care for this population. Cancer 2015;121:605–613. © 2014 American Cancer Society . Abstract : Follow‐up care is critical for childhood cancer survivors who are at high risk for comorbidities and late effects of cancer treatments. Among 193 recently treated childhood cancer survivors, those who were Hispanic, older, or missing health insurance were at higher risk for lacking cancer follow‐up care.